The Effect of Instagram Social Media on Improving Reproductive Health Behavior Among Students of SMK Negeri 1 Labuan - Sfandy Rusly (PT. Anagata Sembagi Education, 2026)
Adolescent reproductive health remains a critical public health issue, particularly in Indonesia, where limited knowledge and unstructured health education continue to expose adolescents to reproductive health risks. This study aimed to determine the effect of Instagram social media on improving reproductive health behavior, encompassing knowledge, attitude, action, and motivation among students of SMK Negeri 1 Labuan, Donggala Regency, Central Sulawesi. A preliminary survey of 80 students revealed that only 41.3% had good reproductive health knowledge, 47.5% showed permissive attitudes toward risky behavior, and 87.5% had active Instagram accounts, yet no structured reproductive health education via social media had been implemented. A quasi-experimental study using the Nonequivalent Control Group Design was conducted from March to May 2026, involving 132 students divided equally into an intervention group (n=66) and a control group (n=66) through purposive sampling. The intervention consisted of structured Instagram-based reproductive health education delivered over six weeks. Data were collected using validated pre-post-test questionnaires and analyzed using the Wilcoxon Signed Ranks Test, Paired t-test, Mann–Whitney U Test, and multiple linear regression. The intervention group demonstrated highly significant improvements across all variables: knowledge (Z=−7.074, p=0.000), attitude (Z=−7.077, p=0.000), action (Z=−7.091, p=0.000), and motivation (Z=−7.078, p=0.000), while the control group showed no significant changes. Multiple linear regression confirmed that group assignment was the sole significant predictor of reproductive health action (B=25.322, R²=0.949, p=0.000). Instagram-based health education is an effective, scalable strategy for improving adolescent reproductive health behavior.